Tensile Strength of Natural Fiber in Different Types of Matrix - Saidi, Taufiq; Hasan, Muttaqin; Amalia*, Zahra (Graduate School of Universitas Syiah Kuala, 2022)
In recent years, product-based products with low environmental impact have become one of the considerations in the construction structure. The attention of researchers toward the development of natural materials has been increasing. The use of natural fibers as composite materials for the strengthened structure has been studied. However, natural fibers are influenced by their hydrophilic nature and specific morphology. Thus, research on natural fiber composite materials still needs to be explored. This study evaluates the tensile strength of natural fiber composite materials based on the type of fiber, fiber layer used, and resin type according to ASTM D3039. The highest tensile strength was found in the epoxy resinbased matrix composite with three layers of abacaa fiber (SAAE-LP3) by 111.45 MPa. The results show that the type of fiber, fiber layer used, and resin in the composite matrix considerably affect its tensile strength performance.